How Does Anesthesia Type Affect Maternal Complications (Hypotension, Respiratory Depression) and Neonatal Outcomes (Apgar Scores, Umbilical Cord Ph) in Women Undergoing Cesarean Delivery? A Systematic Review - Wibowo Suryo Pambudi; Bimo Nugroho Sakti; Ilham Ghifari (International Medical Journal Corp. Ltd, 2026)
Introduction: The global rise in cesarean delivery rates necessitates optimization of anesthetic techniques to improve maternal and neonatal outcomes. Despite numerous comparative studies, uncertainty persists regarding the optimal anesthesia strategy for cesarean delivery across different clinical contexts. Methods: This systematic review synthesized evidence from 76 studies published, comprising randomized controlled trials, etc. Studies were included if they compared anesthesia types for cesarean delivery and reported maternal outcomes (hypotension, blood loss, respiratory depression) or neonatal outcomes (Apgar scores, umbilical cord blood gases). Data were extracted on study characteristics, patient populations, anesthesia techniques, and outcome measures. Harvard citation style was applied throughout. Results: Regional anesthesia, particularly spinal techniques, was associated with significantly higher 1-minute Apgar scores (mean difference 0.58 points; 95% CI 0.36-0.79; p<0.001) and reduced need for neonatal respiratory support (RR 0.62; 95% CI 0.40-0.94; p=0.03) compared to general anesthesia. By 5 minutes, Apgar differences diminished but remained significant (MD 0.09; p<0.001). Umbilical artery pH showed inconsistent differences between techniques, with values generally within normal ranges. Spinal anesthesia was associated with higher hypotension incidence (25-80%) versus epidural (23%) or general anesthesia (2-13%). General anesthesia was associated with increased blood loss (mean difference 75.8 mL), higher transfusion requirements, and greater postoperative pain. Norepinephrine demonstrated superior hemodynamic stability compared to phenylephrine with less bradycardia (RR 0.44). In high-risk populations (preeclampsia, placenta previa, fetal growth restriction), outcomes were predominantly determined by underlying pathology rather than anesthesia technique per se. Conclusion: Regional anesthesia is the preferred technique for most cesarean deliveries due to superior neonatal transition profiles and reduced maternal morbidity. General anesthesia remains essential for specific indications where rapid delivery is required or neuraxial techniques are contraindicated. Optimal outcomes require individualized risk stratification and proactive hemodynamic management.